2021
DOI: 10.3390/agronomy11020241
|View full text |Cite
|
Sign up to set email alerts
|

Consequences and Mitigation Strategies of Abiotic Stresses in Wheat (Triticum aestivum L.) under the Changing Climate

Abstract: Wheat is one of the world’s most commonly consumed cereal grains. During abiotic stresses, the physiological and biochemical alterations in the cells reduce growth and development of plants that ultimately decrease the yield of wheat. Therefore, novel approaches are needed for sustainable wheat production under the changing climate to ensure food and nutritional security of the ever-increasing population of the world. There are two ways to alleviate the adverse effects of abiotic stresses in sustainable wheat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(65 citation statements)
references
References 271 publications
2
60
0
3
Order By: Relevance
“…In recent years, a growing amount of research has been conducted to investigate the impact of multiple stress factors on crop growth and productivity [7,[11][12][13][14]. Various techniques such as proper agronomic practices (e.g., pest management, soil fertility management, and seed priming), traditional breeding, and modern biotechnology have been employed to enhance crop tolerance to abiotic stresses [15][16][17]. Traditional breeding methods such as hybridization and selection, as well as mutation breeding, have contributed considerably to the generation of stress-tolerant crops [16,[18][19][20][21][22]; however, the process is fairly time-consuming.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a growing amount of research has been conducted to investigate the impact of multiple stress factors on crop growth and productivity [7,[11][12][13][14]. Various techniques such as proper agronomic practices (e.g., pest management, soil fertility management, and seed priming), traditional breeding, and modern biotechnology have been employed to enhance crop tolerance to abiotic stresses [15][16][17]. Traditional breeding methods such as hybridization and selection, as well as mutation breeding, have contributed considerably to the generation of stress-tolerant crops [16,[18][19][20][21][22]; however, the process is fairly time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques such as proper agronomic practices (e.g., pest management, soil fertility management, and seed priming), traditional breeding, and modern biotechnology have been employed to enhance crop tolerance to abiotic stresses [15][16][17]. Traditional breeding methods such as hybridization and selection, as well as mutation breeding, have contributed considerably to the generation of stress-tolerant crops [16,[18][19][20][21][22]; however, the process is fairly time-consuming. The 'omic' biotechnologies (e.g., transcriptomics, proteomics, and genomics) can be used to identify the genes that are associated with stress tolerance in crops.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [146] confirmed that canola genotypes with higher S usage efficiency (SUE) could effectively withstand drought stress. Similarly, drought tolerance was also observed in wheat following increased K accumulation [147]. In a recent study, Jia et al [130] performed ionomic and metabolomic analyses of Malus halliana during saline-alkali stress, which caused ion imbalance and Na + toxicity.…”
Section: Ionomics For Enhancement Of Abiotic Stress Resilience In Cropsmentioning
confidence: 99%
“…It provides substantially more protein per gram (12-15%) than rice or maize (2-3%), making it a superior grain [79], but despite this, its output is much lower than those of rice and corn [80]. Extreme abiotic stresses such as drought, high temperature, and salinity, among others, will reduce wheat output by 20%-30%, especially in developing countries [81]. Wheat yields are negatively impacted by stress throughout the reproductive stage of the plant [82].…”
Section: Epigenetic Modifications For Adaptation To Abiotic Stress Tolerancementioning
confidence: 99%